PENGARUH KONSUMSI DAUN BINAHONG TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - La Ode Alifariki (NHM PRESS, 2023)
Hypertension or high blood pressure is a medical condition characterized by increased contractions. Arteries that exceed 140/90 mmHg at rest are confirmed to have high blood pressure. Non-pharmacological treatment of hypertension can use herbal plants, such as binahong leaves. The purpose of this study was to determine the effect of giving binahong leaves on blood pressure in patients with hypertension. This study was limited from 2019 to 2023 and found 4 eligible articles sourced from the Google Scholar search engine with the keywords “Binahong, blood pressure AND hypertension. The results of the study reported that from 4 articles found binahong leaves was effective in lowering blood pressure in patients with hypertension.